Neither villain nor victim : empowerment and agency among women substance abusers - Anderson, Tammy L., 1963- (Critical issues in crime and society., 2008)
Female drug addicts are often stereotyped either as promiscuous, lazy, and selfish, or as weak, scared, and trapped into addiction. These depictions typify the?pathology and powerlessness? narrative that has historically characterized popular and academic conversations about female substance abusers. Neither Villain Nor Victim attempts to correct these polarizing perspectives by presenting a critical feminist analysis of the drug world. By shifting the discussion to one centered on women?s agency and empowerment, this book reveals the complex experiences and social relationships of women addi.